KAJIAN OPTIMASLISASI KINERJA PEMASARAN MENGGUNAKAN MODEL SELLING-IN (Studi Kasus Pada Outlet UKM ‘Marning JOSSS’ di Kabupaten Rembang) - Maslichan Maslichan; Siti Alliyah (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2020)
The study entitled the study of marketing performance optimization using a selling-in model (a case study at the 'Marning Josss' UKM outlet in Rembang Regency) aims to create a new selling-in model by taking into account the selling-in factors that are expected to improve the company's sales performance. The expected target in this research is to get a concrete picture of the marketing performance improvement strategy of Marning Josss UKM Outlets in Rembang Regency, which will be used as a reference for business improvement in developing UKM. The study population included all Marning Josss UKM Outlets in Rembang Regency. Determination of the sample in this study was carried out using a random sampling technique that was purposive in choosing Marning Joss UKM Outlets with established criteria, which were spread in Kaliori District, Rembang District, Lasem District, Sluke District, Kragan District, Sarang District, Sulang District, Sale District, Sedan District, Pamotan District, Pancur District, Gunem District, Bulu District and Sumber District. The respondents were managers or Outlet owners who sold Marning Josss UKM products. The analysis technique used in this study is a model of causality or influence and relationships. The analytical tool used in processing data to test the proposed hypothesis is to use the UKM (Structural Equation Model) which is operated through the AMOS (Analysis of Moment Structure) program. The results showed that the selling-in performance could only have a direct effect on improving the marketing performance of the 'Marning JOSSS' UKM Outltet in Rembang district if there was an increase in customer relationships and good communication